PENGARUH TINGKAT PENGANGGURAN, KONSUMSI RUMAH TANGGA, DAN TENAGA KERJA TERHADAP KEMISKINAN DI INDONESIA - Darmawan, I Gusti Ngurah Gede Agung Indra; Ayuningsasi, Anak Agung Ketut (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 10 No 12 (2021): VOL 10 NO 12, DESEMBER 2021 [4563 - 5005], 2022)
The main problem faced by developing countries is poverty. Poverty is a complex and multidimensional problem so that it becomes a development priority. The purpose of this study is to analyze (1) the simultaneous effect of the unemployment rate, household consumption, and labor on poverty in Indonesia, and (2) the partial effect of the unemployment rate, household consumption, and labor on poverty in Indonesia. This research was conducted in the territory of the Republic of Indonesia, the data sources are from the Central Statistics Agency (BPS) and Bank Indonesia. The data collection method used in this study is the observation method with multiple linear regression analysis techniques. The number of observations is 32 provinces in the period 2015 – 2019. The results of th is study show that (1) the unemployment rate, household consumption , and labor simultaneously have a significant effect on poverty in Indonesia, (2) the unemployment rate has a positive and significant effect on poverty in Indonesia. Indonesia, (3) household consumption has a positive and significant effect on poverty in Indonesia, and (4) labor has a negative and significant effect on poverty in Indonesia. Keywords: Poverty, Unemployment Rate, Household Consumption, Labor.